Dispositional Mindfulness and Aggression Among Women in Residential Substance Use Treatment. (6th December 2015) - Shorey, Ryan C.; Elmquist, JoAnna; Anderson, Scott E.; Stuart, Gregory L.
Abstract : There is a large literature on substance misuse and interpersonal aggression, including aggression perpetrated by women in treatment for substance misuse. There is also a growing body of literature on mindfulness and substance use, as well as mindfulness and aggression. However, to date, there has been little research on whether dispositional mindfulness is associated with increased aggression among women in treatment for substance misuse. The current study, therefore, examined whether dispositional mindfulness was associated with aggression, above and beyond substance use and demographic characteristics, in women in residential substance misuse treatment ( N = 137). Results showed that lower dispositional mindfulness was associated with increased aggression (physical, verbal, and aggressive attitude). Moreover, this relationship between dispositional mindfulness and aggression remained even after controlling for alcohol problems, drug problems, and age, all known predictors of aggression. Our results provide the first empirical evidence that dispositional mindfulness is negatively associated with aggression in women in treatment for substance misuse. Pending replication, this could have important implications for treatment. Specifically, mindfulness-based interventions may prove helpful for the concurrent treatment of substance misuse and aggression.